2007
DOI: 10.1007/s11524-007-9183-5
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention and Control of HIV/AIDS, TB and Vector-borne Diseases in Informal Settlements: Challenges, Opportunities and Insights

Abstract: Today_s urban settings are redefining the field of public health. The complex dynamics of cities, with their concentration of the poorest and most vulnerable (even within the developed world) pose an urgent challenge to the health community. While retaining fidelity to the core principles of disease prevention and control, major adjustments are needed in the systems and approaches to effectively reach those with the greatest health risks (and the least resilience) within today_s urban environment. This is part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…Significantly, health care is particularly absent in slum areas. As expected, TB is common in urban slums (David, Mercado, Becker, Edmundo, & Mugisha, 2007), and resistant strains are also common -perhaps increasingly so (Githui et al, 2004).…”
Section: Introductionmentioning
confidence: 55%
“…Significantly, health care is particularly absent in slum areas. As expected, TB is common in urban slums (David, Mercado, Becker, Edmundo, & Mugisha, 2007), and resistant strains are also common -perhaps increasingly so (Githui et al, 2004).…”
Section: Introductionmentioning
confidence: 55%
“…A scoping review was found that summarized the impact of urbanization on the epidemiology of infectious diseases, including some VBDs in tropical countries and the emergence of infectious diseases over time [20]. Given that urbanization increasingly affects the epidemiological characteristics of infectious diseases, more research is needed to study the VBD-specific effects of urbanization.…”
Section: Health Interventions For the Prevention And Control Of Vbdmentioning
confidence: 99%
“…Holtgrave also noted that the opt-out approach may not address racial/ethnic health disparities because HIV disproportionately affects communities of color, such as the African American community. More specifically, David, Mercado, Becker, Edmundo, and Mugisha (2007) addressed the needs of those living in slums and similar situations in urban areas, noting that these individuals needed to be provided with opportunities equal to those of the rest of the population to access proven interventions. Even with these newer data, Valdiserri (2007) cautioned that prevention efforts should not be limited to only opt-out and targeted testing methods.…”
Section: Review Of the Literature Universal Testingmentioning
confidence: 99%